(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: HPVs infect stratified epithelium and establish infections that can persist for decades. For these infections to persist, papillomaviruses have evolved strategies to evade the effects of the innate immune system during the initial phases of infection as well as long-term surveillance by the adaptive immune system. Warts are the cutaneous manifestations of HPV infection. Warts may exist in different forms according to the epithelial surface and HPV type responsible for the infection.Common warts (Verruca vulgaris), plantar warts (Verruca plantaris), flat or plane warts (Verruca plana) and genital warts (Condyloma acuminata) are some of the clinical manifestations of HPV infection. There are numerous immunomodulators that have been used for treating warts. Although topical mmunotherapy agents have their own clinical advantages over other destructive treatment modalities, an updated assessment of these agents is required.